Les partenaires ludiques des enfants en situation de handicap - Ludovic Blin
In this article, based on ethnographic research, we will be interested in people, peers or adults, playing with children with cognitive/physical disabilities, in two social spaces: school and parental home. We will also see how difficult it is for a child with a disability to find a playful partner and take part  in play.